Health-related quality of life in children born preterm at school age: the mediating role of social support and maternal stress - Martínez-Shaw, Melissa Liher; Evensen, Kari Anne I.; Melero, Sandra; Sánchez-Sandoval, Yolanda (Frontiers in Psychology, 2024)
Research on health-related quality of life (HRQoL) of school-aged children born preterm (< 37 weeks of gestational age) is scarce and there are few studies examining the relationship with medical and family factors. The aims were to analyse HRQoL in a sample of 8-year-old children born preterm with very low birth weight (VLBW), to test a proposed theoretical model that examines the relationship with medical and socio-family factors, and to explore the mediation effects of maternal factors between perinatal variables, demographic characteristics and HRQoL.A total of 147 VLBW children and 116 mothers were assessed. The measures included for assessment were self-and parent-reported HRQoL, functional social support, maternal stress, sociofamily risk index and neonatal medical risk index. Mediation analysis was applied to investigate mediation effects of the maternal factors.Mean self-and parent-reported KIDSCREEN scores were 55.1 (SD 10.1) and 58.2 (SD 9.1), respectively, indicating better HRQoL than the normed sample with a mean of 50 (p < .001). The total effect of the initial theoretical model was not significant, thus another partial model was validated. Socio-family risk index significantly influenced HRQoL (direct effect), and this relationship was mediated by functional social support and maternal stress (indirect effects). School-aged VLBW children and their parents reported better HRQoL than the mean reference value on KIDSCREEN-10 and -27. Maternal stress and social support had a mediating effect on the children's HRQoL. These results could be used to tailor interventions in these families.